Repair of a Salter IV Physeal Fracture of the Humeral Condyle in a Chow-Chow Using a Cannulated Screw - Lewis, D. D.; Elkins, A. D.; Oakes, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
A Salter IV physeal fracture of the humeral condyle in a three-month-old Chow-Chow was repaired using a cannulated screw to provide interfragmentary compression. The fracture was reduced and a Kirschner wire was placed at the level of the olecranon fossa. The AO/ASIF cannulated screw system facilitated screw placement directly over the Kirschner wire, and thus allowed the screw to be placed proximal to the distal humeral growth plate without interfering with elbow extension. Limb and elbow function were normal when the dog was examined eight weeks following surgery. Radiographic union of the fracture had occurred without complication.
Keywords: Humeral condylar fracture; cannulated screw